Nomadic Europe: Spaces, Identities and Politics of Belonging in Post-Socialist Slovenia: Номадска Европа: Просторите, идентитетите и политиките на припадност во постсоцијалистичка Словенија - Horvat, Ksenija Vidmar; Čemerski, Ognen (Identities: Journal for Politics, Gender and Culture, 2007)
Author(s): Ksenija Vidmar Horvat | Ксенија Видмар Хорват Title (English): Nomadic Europe: Spaces, Identities and Politics of Belonging in Post-Socialist Slovenia Title (Macedonian): Номадска Европа: Просторите, идентитетите и политиките на припадност во постсоцијалистичка Словенија Translated by (English to Macedonian): Ognen Čemerski | Огнен Чемерски Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 6, No. 1 (Winter 2007) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 125-163 Page Count: 38 Citation (English): Ksenija Vidmar Horvat, “Nomadic Europe: Spaces, Identities and Politics of Belonging in Post-Socialist Slovenia,” Identities: Journal for Politics, Gender and Culture, Vol. 6, No. 1 (Winter 2007): 125-163. Citation (Macedonian): Ксенија Видмар Хорват, „Номадска Европа: Просторите, идентитетите и политиките на припадност во постсоцијалистичка Словенија“, превод од англиски Огнен Чемерски, Идентитети: списание за политика, род и култура, т. 6, бр. 1 (зима 2007): 125-163.